Implementasi Qa’idah Fiqhiyyah dalam Screening Saham Syariah pada Bursa Efek Syariah Indonesia - Sa'adah, Siti Zumrotus (TAWAZUN: Journal of Sharia Economic Law, 2022)
The Indonesian Ulema Council in Fatwa DSN No. 40/DSN-MUI/X/2003 has issued a fatwa on the idolatry of sharia stocks. But in the fatwa MUI only provides an explanation of the criteria for the type of effect that can be categorized as a sharia effect and what transactions should not be done in stocks globally without explaining the concept of reference fiqh in the screening process of sharia shares. This research wants to uncover the facts of fiqh buried in the classical books. This research aims to find out the concept of fiqh which is a reference for the establishment of Islamic law in the process of screening sharia shares, and how to use the concept of fiqh in determining the criteria for screening sharia stocks. This research uses qualitative methods, taking primary data from the DSN-MUI fatwa document and OJK regulations, then linking these theories to the concept of fiqh used by classical scholars in determining Islamic sharia law This study concluded that the criteria for shari'a stocks on the Indonesia Stock Exchange refer to fiqh concepts including the concepts of "ghalabah al-dzann", "ikhthiyath", "lil aktsar hukmal kulli", as well as other derivative concepts.